1979
DOI: 10.1042/bj1770139
|View full text |Cite
|
Sign up to set email alerts
|

Measurement in vivo of hydrogenase-catalysed hydrogen evolution in the presence of nitrogenase enzyme in cyanobacteria

Abstract: A method was devised that allows measurement in vivo of hydrogenase-catalysed H2 evolution from the cyanobacterium Anabaena cylindrica, independent of nitrogenase activity, which is also present. Addition of low concentrations of reduced Methyl Viologen (1-10mM) to intact heterocystous filaments of the organism resulted in H2 evolution, but produced conditions giving total inhibition of nitrogenase (acetylene-reducing and H2-evolving) activity. That the H2 formed under these conditions was not contributed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 12 publications
4
21
0
Order By: Relevance
“…In seven days, this strain produced 770 ml hydrogen/g dry cells (0.205,umol/mg cells/hr). Anabaena eylindriea, 13) Mastigoẽ ladus laminosus 14 ) and Oseil/atoria sp. Miami BG-7 9 ) produce hydrogen in closed vessels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In seven days, this strain produced 770 ml hydrogen/g dry cells (0.205,umol/mg cells/hr). Anabaena eylindriea, 13) Mastigoẽ ladus laminosus 14 ) and Oseil/atoria sp. Miami BG-7 9 ) produce hydrogen in closed vessels.…”
Section: Resultsmentioning
confidence: 99%
“…This may be a consequence of the fact that the ferric ion is a component of Fe-protoporphyrine, which is an intermediate in the phycocyanin system. 13 ) Table III shows the optimum conditions for hydrogen production by Lyngbya sp. (No.…”
Section: Resultsmentioning
confidence: 99%
“…Other workers have reported H, formation from non-heterocystous species (Weare & Benemann, 1974;Mitsui & Kumazawa, 1977), marine (Lambert & Smith, 1977;Mitsui & Kumazawa, I 977) and thermophilic (Miyamoto, Hallenbeck & Benemann, I 979 a ) cyanobacteria. Anabaena CA, a rapidly growing and rapidly nitrogen-fixing thermophilic cyanobacterium (Stacey et al,) does not produce significant H, in either an argon/CO, or an air/CO/C,H,/CO, gas phase (G. D. S., unpublished observation), while Anabaena sp.…”
Section: ( a ) Species And Strainsmentioning
confidence: 93%
“…Some variability is seen in the level of CO, used for the growth of A . cylindrica, frequently being either 0.3 yo (Benemann & Weare, 1 9 7 4~; Lambert et al, 1979~) or 5 % Tel-Or et al, 1978) by volume. However, detailed studies revealed this variation not to be a factor responsible for variable rates of H, formation reported by these various workers .…”
Section: (B) Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation